Current status of minimally invasive management of pediatric upper urinary tract calculi - Kolla Surendra; Wadhwa Pankaj; Aron Monish (Wolters Kluwer Medknow Publications, 2006)
The surgical management of pediatric upper urinary tract calculi has evolved from open surgery to minimally invasive techniques. With advancement in instrumentation, endourological procedures are being performed more commonly in children. However, the endourological management of renal and ureteral stones in the pediatric population is considered challenging, owing to the smaller size of the urinary tract. Various minimally invasive techniques that are being applied in the management of pediatric urolithiasis, include shock wave lithitripsy (SWL), percutaneous nephrolithotomy (PCNL), ureterorenoscopy and a combination of these procedures. The role of SWL is well established and is considered the first line of treatment in the management of urinary calculi in pediatric patients. Recent reports have confirmed the safety of PCNL and ureteroscopy in children, although they are not as widely practiced in children as in adults. This article reviews literature published till October 2005, pertaining to the minimally invasive management of pediatric upper urinary tract calculi.